Investigation of natural frequency and critical speed for Jeffcott rotor system - Hnin, Mya Thet; Htike, Thein Min (Journal of Research and Applications in Mechanical Engineering, 2020)
In the rotating machinery, the critical speed is one of the most important parameters that must be evaluate. In general, it is very important to determine the critical speed to avoid the breakdown of rotating machine. In this study, the purpose is to investigate critical speed and natural frequency of the rotor bearing system. Firstly, the dynamic characteristics of the rotor are identified. And then, the critical speed of the rotor is evaluated. The finite element model of the rotor is modelled in COMSOL Multiphysics software. The experiment is conducted to determine the natural frequencies of rotor bearing system. In the comparison of natural frequency, the maximum discrepancy is 9.47%which occurs at third mode. The discrepancy between theoretical and numerical simulation results of critical speed is less than 6%. Critical speed analysis is important for stable operation of rotating machine.